Esophageal cancer screening in achalasia: is there a consensus?. Issue 3 (1st April 2015) - Ravi, K.; Geno, D. M.; Katzka, D. A.
Summary: Achalasia is an important but relatively uncommon disorder. While highly effective therapeutic options exist, esophageal cancer remains a long-term potential complication. The risk of esophageal cancer in achalasia remains unclear, with current guidelines recommending against routine endoscopic screening. However, given limited data and conflicting opinion, it is unknown whether consensus regarding screening practices in achalasia among experts exists. A 10-question survey to assess screening practices in achalasia was created and distributed to 28 experts in the area of achalasia. Experts were identified based on publications and meeting presentations in the field. Survey responses were received from 17 of 28 (61%) experts. Wide geographic distribution was seen among respondents, with eight (47%) from Europe or Australia, seven (41%) from the United States, and two (12%) from Asia. Screening for esophageal cancer was inconsistent, with nine (53%) experts endorsing the practice and eight (47%) not. Screening practices did not differ among geographic regions. No consensus regarding the risk for esophageal cancer in achalasia was seen, with three experts reporting no increased risk compared with the general population, eight experts a lifetime risk of 0.1–0.5%, three experts a 0.5–1% risk, two experts a 1–2% risk, and one expert a 3–5% risk. However, these differences in perception of risk did not influence screening practices. Upper endoscopy was utilized among all experts who endorsed screening. However, practices still varied with screening commencing at or within 1 year of diagnosis in two practices compared with 5 and 10 years in three respective practices each. Surveillance intervals also varied, performed every 2 years in four practices, every 3 years in four practices, and every 5 years in one practice. Practice variation in the management of achalasia itself was also seen, with initial treatment with Heller myotomy endorsed by eight experts, pneumatic dilation by five experts, and two each endorsing peroral endoscopic myotomy or no specific preference. In addition, while 82% (14/17) of experts endorsed long-term follow up of patients, no consensus regarding long-term follow up existed, with annual follow up in eight practices, every 3–6 months in three practices, and every 2 years in three practices. Large practice variation in the long-term management of achalasia exists among experts in the field. Only a slight majority of experts endorse screening for esophageal cancer in achalasia, and no consensus exists regarding how surveillance should be structured even among this group. Interestingly, the lack of consensus on cancer screening parallels a lack of agreement on initial treatment of achalasia. These findings suggest a need for greater homogeneity in the management of longstanding achalasia and cancer screening. Further, this study highlights the need for more data on this topic to foster greater agreement.